THE POWERFUL IMPACT OF SCHOOL PRINCIPAL LEADERSHIP AND TEACHER PROFESSIONALISM ON ENHANCING TEACHER PERFORMANCE DURING THE COVID-19 PANDEMIC IN SURABAYA - Rahayu, Puji; Gani, Abdul Juli Andi; Suryadi, Suryadi (Erudio Journal of Educational Innovation, 2025)
The COVID-19 pandemic disrupted integrated learning in schools due to limited resources, compressed schedules, and stakeholder unpreparedness. School principals emerged as critical leaders, enhancing education quality through technology integration, teacher training, and innovative solutions. Despite efforts, challenges like internet access and teacher shortages persist, requiring policy and infrastructural reforms. This study, conducted in Surabaya, investigates the influence of principal leadership and teacher professionalism on enhancing teacher performance. Using quantitative methods and data from 73 respondents, the findings highlight the significant role of leadership in improving teacher effectiveness and education quality during crises. This study highlights the critical role of principal leadership in improving teacher performance, with significant evidence showing its direct impact. While teacher professionalism is important, its influence on performance is less pronounced, indicating the need for strategies to align professionalism with effective teaching. Challenges during the COVID-19 pandemic underscored the value of strategic leadership in supporting educators. Effective principals foster motivation and professionalism, driving better teacher and student outcomes. The findings call for leadership development, targeted teacher training, and further research to address gaps and enhance education quality.THE POWERFUL IMPACT OF SCHOOL PRINCIPAL LEADERSHIP AND TEACHER PROFESSIONALISM ON ENHANCING TEACHER PERFORMANCE DURING THE COVID-19 PANDEMIC IN SURABAYA